As práticas de letramento da família e as dificuldades de aprendizagem: perspectivas para o debate - Oliveira, Patrícia de (2012)
The object of this research were qualitative ethnomethodological approach to the literacy practices of parents of children with learning difficulties in order to understand what values and beliefs could be underlying their practices and literacy events that give children. Literacy can be understood as the ability to handle different bearers text, making social uses of written language. During the development process to literacy skills, the way the family makes use of written language can be crucial to a child who is building his own literacy process, leading her to succeed or difficulties in school learning. This research involved the participation of parents of children with learning difficulties in a public school in a small city in the interior of Sao Paulo .. To collect the data were organized 10 meetings, being 1 per week, lasting approximately 1 hour and 30 minutes. At these meetings, the researcher read children's stories and perspectives presented for participants to read to their children at home. The participants reported their experiences with written language and how was the way that promoted literacy events for their children. The meetings were recorded in audiovisual and transcribed for analysis. The analyzes showed 3 categories for study: the literacy events that participants experienced in their childhood, their literacy practices, and literacy events that lead to their children. The data showed that families has been providing their children with literacy events consonants needs and beliefs and making use of accessible technologies of information and communication, allowing the children to enter a world of letters corresponding to these needs and beliefs, but so other conventional forms of reading and writing.